T1‐/T2‐weighted ratio differs in demyelinated cortex in multiple sclerosis. Issue 4 (21st September 2017) - Nakamura, Kunio; Chen, Jacqueline T.; Ontaneda, Daniel; Fox, Robert J.; Trapp, Bruce D.
Abstract : Detecting cortical demyelination in patients with multiple sclerosis (MS) is difficult. Using magnetic resonance imaging (MRI), ratio maps of T1‐weighted (T1w) and T2‐weighted (T2w) images may be sensitive to cortical myelin levels. In this MRI–histological study, postmortem in situ scans were acquired from 6 cadavers with MS on a 3T MRI machine. Immunocytochemistry was used to correlate myelin status and cortical T1w/T2w measures. The results showed that the T1w/T2w values significantly differed between demyelinated and myelinated cortex ( p < 0.001). The T1w/T2w ratio maps may be a relatively simple, clinically feasible method to assess cortical demyelination. Ann Neurol 2017;82:635–639